Genetically predicted telomere length is not associated with pancreatic cancer risk - Antwi, Samuel O. (Cancer Epidemiol Biomarkers Prev, 2017)
BACKGROUND: Epidemiologic associations of leukocyte telomere length (LTL) and pancreatic ductal adenocarcinoma (PDAC) have been inconsistent owing, in part, to variation in telomere length (TL) assessment across studies. To overcome this limitation and address concerns of potential reverse causation, we used carriage of telomere-related alleles to genetically predict TL and examined its association with PDAC. METHODS: A case-control study of 1,500 incident PDAC cases and 1,500 controls, frequency-matched on age and sex was performed. Eight of nine single nucleotide polymorphisms (SNPs) previously associated with variation in LTL were analyzed. Genetic risk scores (GRS) consisting of the TL-related SNPs were computed as the number of long TL alleles carried by an individual scaled to published kilobase pairs of TL associated with each allele. Participants were further categorized based on the number of short TL alleles they carry across all eight SNPs. Associations were examined in additive and dominant models using logistic regression to calculate odds ratios (ORs) and 95% confidence intervals (CIs). RESULTS: In age- and sex-adjusted models, one short TL allele (rs10936599, T) was associated with reduced risk, whereas another short TL allele (rs2736100, A) was associated with increased risk, with per-allele ORs of 0.89 (95% CI: 0.79–0.99) and 1.13 (95% CI: 1.01–1.24), respectively. No association was observed with GRS or short TL allele counts, and no associations were observed in the dominant models. CONCLUSIONS: The findings suggest that genetically predicted short TL is not associated with PDAC risk. IMPACT: Common genetic determinants of short TL do not appear to influence PDAC risk.